Uma compreensão psicanalítica acerca da infidelidade conjugal - Reghelin, Michele Melo (Universidade do Vale do Rio dos Sinos, 2011)
This Master thesis explores the subject of couple infidelity using psychoanalysis. It provides an in-depth comprehension of the psychological mechanisms involved on a loving-unfaithful couple relationship. Based on the contemporary works of Otto Kernberg (1995a, 1995b), Lucinda Mitchell (2000) and Lawrence Josephs (2006), conflicts derived from loving relationships are studied. A qualitative methodology was used to formulate a psychodynamic comprehension of two case studies. Data was obtained through psychoanalytical short term psychotherapy and through the results from Object Relations Test (Phillipson, 2008). The study identified that long term infidelity has its origins in pre-oedipal issues related to the avoidance of deepening the romantic relationship and to the frightening experience of losing primitive parental objects. This article aims at improving the theoretical framework to study loving relationships, as well as the clinical practice of psychoanalytical psychotherapy.
Keywords: Infidelidade conjugal; Amor; Relações conjugais; Psicanálise; Teste das relações objetais; Couple’s infidelity; Love; Couple’s relationship; Psychoanalysis; Object relations test; ACCNPQ::Ciências Humanas::Psicologia